2012
DOI: 10.1371/journal.pone.0050913
|View full text |Cite|
|
Sign up to set email alerts
|

Pathway Analysis of Smoking Quantity in Multiple GWAS Identifies Cholinergic and Sensory Pathways

Abstract: Cigarette smoking is a common addiction that increases the risk for many diseases, including lung cancer and chronic obstructive pulmonary disease. Genome-wide association studies (GWAS) have successfully identified and validated several susceptibility loci for nicotine consumption and dependence. However, the trait variance explained by these genes is only a small fraction of the estimated genetic risk. Pathway analysis complements single marker methods by including biological knowledge into the evaluation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 44 publications
0
9
0
1
Order By: Relevance
“…CHRNB4 , CHRNA1 , CHRNA 3, CHRNA5, and CHRNA7 ), glutaminergic (e.g., GRM7 and GRM8 ) and dopaminergic (e.g., DRD1 , DRD2 , DRD3 , DRD4 , and DRD5 ) systems, and (3) reuptake and vesicular packaging of neurotransmitters (e.g., SLC6A4 , SLC18A2 , and SLC9A9 ) related to learning and memory (Harari et al, 2012; Liu, Fan, Liu, Cheng, & Wang, 2015; Minica et al, 2017; Yang and Li, 2016; Begum et al, 2016). Consequently, genetic association studies of alcohol as well as nicotine dependence highlight the complex nature of addiction as an outcome with physiological aspects including drug metabolism and availability within the body and brain, as well as neurobiological mechanisms related to the development of addiction.…”
Section: Genetic Association Studiesmentioning
confidence: 99%
“…CHRNB4 , CHRNA1 , CHRNA 3, CHRNA5, and CHRNA7 ), glutaminergic (e.g., GRM7 and GRM8 ) and dopaminergic (e.g., DRD1 , DRD2 , DRD3 , DRD4 , and DRD5 ) systems, and (3) reuptake and vesicular packaging of neurotransmitters (e.g., SLC6A4 , SLC18A2 , and SLC9A9 ) related to learning and memory (Harari et al, 2012; Liu, Fan, Liu, Cheng, & Wang, 2015; Minica et al, 2017; Yang and Li, 2016; Begum et al, 2016). Consequently, genetic association studies of alcohol as well as nicotine dependence highlight the complex nature of addiction as an outcome with physiological aspects including drug metabolism and availability within the body and brain, as well as neurobiological mechanisms related to the development of addiction.…”
Section: Genetic Association Studiesmentioning
confidence: 99%
“…Smoking behavior is partially genetically determined, and at least genome-wide significant associated loci were identified in European ancestry subjects 9 , 10 , where the strongest and most consistent association reported is at the 15q25.1 locus (CHRNA3-CHRNA5-CHRNB4 gene cluster). Genes associated with smoking quantity were enriched for cholinergic receptors, sensory perception of smell, and Retinoid Binding 11 .…”
Section: Introductionmentioning
confidence: 99%
“…The nearest gene to our most strongly associated CNV component on chromosome 3p26.1 deletion region is GRM7 , which is involved with glutamate receptor activation. Several previous GWAS studies of nicotine dependence-related phenotypes have reported associations to markers in GRM7 [ 39 42 ]. Examining gene expression levels of GRM7 in the GTEx portal ( http://www.gtexportal.org/home/gene/GRM7 ) showed higher expression in different parts of brain including the cortex, hypothalamus and hippocampus ( S7 Fig ), which included 84.3% NHW and 13.7% African Americans in their expression analysis.…”
Section: Discussionmentioning
confidence: 99%